THE EFFECT OF LEVERAGE AND FIRM SIZE ON TAX AVOIDANCE WITH PROFITABILITY AS MODERATING - Muhammad Sopiyana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to analyze the effect of leverage and firm size on tax avoidance and profitability as moderating variables and determine which variables have a dominant influence by collecting data on the publication of annual financial statements of construction companies that have been listed on the IDX and in accordance with the sample selection criteria. The independent variables are leverage, firm size, the dependent variable is tax avoidance and profitability as a moderator. The type of research used in this research is quantitative data. Sources of data used in this study is secondary data. Determination of the sample of this study using purposive sampling, namely the purpose of the sample to obtain a representative sample in accordance with the criteria of construction companies listed on the Indonesia Stock Exchange in 2017-2019. The data obtained from the IDX are then processed and analyzed using the regression method using the e-views version. The results of this study indicate that the leverage variable has no significant effect on tax avoidance, the firm size variable has a negative and significant effect on tax avoidance. This is not followed by the variable leverage and firm size which moderated profitability has no significant effect on tax avoidance.